Sampled-based consensus of multi-agent systems with bounded distributed time-delays and dynamic quantisation effects. Issue 11 (18th August 2022) - Yu, Luyang; Cui, Ying; Liu, Yurong; Alotaibi, Naif D.; Alsaadi, Fawaz E.
Abstract : In this paper, we are concerned with the sampled-based consensus problem of multi-agent systems with bounded distributed time-delays and quantisation effects. A dynamic quantisation scheme is introduced to save the constrained communication resources, where some adjustable parameters are introduced to exclude the phenomena of quantiser saturation. In addition, to reduce the actuation burden of controller and quantiser cost, a sampled-data control strategy is employed to investigate the consensus problem. Several sufficient criteria are derived to achieve consensus of multi-agent systems based on the matrix theory and Lyapunov control techniques. Finally, two numerical examples are provided to demonstrate the effectiveness of the derived results.